Pengaruh Tingkat Pendidikan dan Disiplin Kerja Terhadap Kinerja Personel Puslitbang Polri - Agni Andini, Sifa (Jurnal Litbang Polri, 2025)
The Indonesian National Police Research and Development Center identified issues such as a lack of educational information, a tendency toward declining personnel discipline, and suboptimal personnel performance. Therefore, this study aims to determine the influence of educational level and work discipline on personnel performance. This study is quantitative in nature, using a quota sampling technique to select 64 personnel consisting of non-commissioned officers and first officers (Pama) in the Indonesian National Police, grades II A – III C for civil servants in the Indonesian National Police, by collecting data through observation, questionnaires, and interviews as a supplement to enhance research understanding. The results of validity and reliability tests indicate that all research statements are valid and reliable. Classical assumption tests have been met, including normality tests, multicollinearity tests, and heteroskedasticity tests. Multiple linear regression analysis reveals that the variables of educational level and work discipline have a positive and significant influence on personnel performance. Partial hypothesis testing (t-test) shows that educational level and work discipline have significant values from the variables Educational Level X1 and Work Discipline X2 on Performance Y. Similarly, simultaneously (F-test), educational level and work discipline variables together have a significant influence on the performance of Puslitbang Polri personel.